Unverricht-Lundborg Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The progression of clinical and neurophysiological findings in a Swedish family with 4 siblings with Unverricht-Lundborg disease is reported from the Departments of Pediatrics and Clinical Neurophysiology, University of Gothenburgh, Sweden and Department of Pediatrics, University of Bergen, Norway.